An Investigation on the Ultimate Strength of Cold-Formed Steel Bolted Connections - Konkong, N. (Engineering, Technology & Applied Science Research, 2017)
This paper presents experimental results and finite element analysis of the cold-formed steel bolted connection under shear loading. Experiments are conducted to study the ultimate behaviors, such as ultimate strength and failure mode of connections. The samples were fabricated into three different groups, single bolted, double bolted and quadruple bolted connection. Material properties were determined by tensile coupon testing. Bearing failure modes were detected in the bolted connection tests. The ultimate capacities were compared with the nominal strengths calculated using the AISI (2012). The comparisons show that the nominal strength parameters predicted by this specification is conservative. The finite element analysis shell elements were used to model the cold-formed steel plate while solid elements were used to model the bolted fastenings for the purpose of studying the structural behavior of bolted connections. Material nonlinearities, contact problem and geometry nonlinearities analysis are carried out in order to predict ultimate strength and failure mode of connections. The results show that the proposed model accurately represents the failure mode and ultimate strength of bolted connection, as determined from experimental investigation. The new factor for type of bearing connection has a good agreement with the tested bearing strength of bolt connection.